Designing Information System Of Social Media Alumni National University Based On Website: Designing Information System Of Social Media Alumni National University Based On Website - Abdul Aziz Hasibuan; Agung Triayudi; Ratih Titi Komala Sari (Jurnal Mantik, 2020)
Alumnus is someone who has graduated from high school or college and has an important role in showing image and quality, because the alumni association forum is not just a forum for friendship between alumni, but also a forum for discussion and communication in an effort to advance higher education. Until now, alumni of the National University (UNAS) integrate and communicate only through social networks such as WhatsApp and Facebook, so with this web-based internet facility, alumni can utilize and facilitate communication between alumni. This web-based social network is designed not only to connect alumni from the National University (UNAS) but can establish relationships between National University lecturers (UNAS) and can exchange information in various types such as job vacancies, training, professional certification, campus environment activities and information others that are useful for alumni and lecturers of the National University (UNAS). This site was created by first starting the system design using UML then proceed with the creation of a user interface and using the PHP and MySQL programming languages as database management. This site still has some shortcomings both in terms of features and security